(untitled) (Annals of Medical Research, 2022)
Aim: Helicobacter Pylori (HP) is the most common bacteria that cause chronic bacterial infections in humans. We aimed to investigate the possible relationship between HP infection and autoimmune thyroid diseases, as well as the possible relationship between HP density and platelet-to-lymphocyte ratio (PLR) and neutrophil-to-lymphocyte ratio (NLR). Materials and Methods: A total of 3,380 patients who underwent upper gastro intestinal system endoscopy in the our tertiary hospital endoscopy unit between 2010 and 2018 were scanned, and 250 patients who met the inclusion criteria were included in our retrospective study. Results: The study was examined under 2 groups: 104 (41.6%) were HP negative and 146 (58.4%) were positive. While TPOAb was positive in 63 (25.2%) patients, 61 (24.4%) patients were found to be TgAb positive. Atrophy was detected in 11 (4.4%) patients and metaplasia in 20 (8%). There was no statistically significant difference between HP-positive and HP-negative patients in terms of age, gender, Wbc, Hg, Neu, Lymp, Plt, PLR, and NLR (P > 0.05). There was no significant concordance between HP positivity and TPOAb and TgAb positivity. There was no statistically significant relationship between HP density and PLR and NLR (Spearman’s rho correlation analysis, P > 0.05). Conclusion: In conclusion, no relationship was found between HP infection and autoimmune thyroid disease in our study. Similarly, there was no significant relationship between HP density and PLR and NLR.